Evaluating the rumen microbial community of genetically divergent spring-calving dairy cows grazing grass-only or grass-clover swards at different stages of the grazing season - Dwan, Charles; Das, Anubhav; O’Toole, Paul W.; O’Callaghan, Tom F.; Meehan, Dara; Hennessy, Deirdre; Irish, Hannah; Buckley, Frank; Lahart, Ben (Frontiers in Microbiology, 2025)
The current study used a culture-independent methodology to investigate the rumen microbiome composition in two genetically divergent groups of spring-calving dairy cows, high (€218) and low (€157) Economic Breeding Index (EBI), grazing two sward treatments—perennial ryegrass (grass-only) or perennial ryegrass and white clover (grass-clover)—at three time points across spring, summer, and autumn of a single grazing season. The analysis indicated that the EBI status had no significant effect on the rumen microbial community within the statistical power of this study. Beta diversity between the microbiomes was different (p < 0.001) between the two sward treatments only in autumn, when the clover proportion was highest (50.2%). Season had a significant effect on microbiome beta diversity across sward treatments (p < 0.001). There were only minor differences in the composition of the rumen microbiomes between the two sward treatments. Many bacterial genera were differentially abundant between spring and the two later time points. Bacterial genera that were more abundant in spring were positively correlated with rumen propionate levels, while those more abundant in summer and autumn were negatively correlated with propionate and positively correlated with acetate and butyrate. Methanogenic archaeal abundance was greater in summer and autumn compared to spring, and they were negatively correlated with propionate and positively correlated with methane (CH4) production. The results of this study demonstrate that genetic selection using the EBI does not affect the rumen microbial community and the core rumen microbial community is similar in cows grazing either grass-only or grass-clover swards. The results also demonstrate that the rumen bacterial community shifts across the grazing season, providing more favorable conditions for methanogenesis in summer and autumn compared to spring.